Role Played by Coal in the Energy Balances of the Asia-Pacific Countries - Jankowiak, Anna H.; Mazurek, Szymon (Rola węgla w bilansach energetycznych krajów regionu Azji i Pacyfiku, 2010)
The Asia-Pacific region is a much diversified part of the world. Countries of various sizes, populations, religions, cultures, languages, diverse economic systems and varied levels of economic development are situated here. Moreover, this is the region facing dynamic economic development and aspiring to become the economic centre of the world in the near future. First of all, the rising energy demand is satisfied from the most easily accessible sources, thus, in case of numerous Asian countries, it means exploiting coal resources. Even though in the days of calling for reduction of CO2 emissions, one may say that such an approach is unpopular, at the very least, the analysis of the energy balances in the selected countries of the region shows that for a long time coal shall play a significant role as an energy source.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 33-45
Keywords: coal; energy balances; energy diversity